A new oxathiolane fromEnterobacter cloacae - Yap, A.C.; Teoh, W.Y.; Chan, Kok Gan; Sim, Kae Shin; Choo, Yeun Mun (Taylor & Francis, 2015)
Enterobacter cloacae is a versatile bacterial species inhabiting a wide variety of niches and is capable of metabolising a wide variety of substances as energy resources. The fermentation culture of this bacterial species has successfully yielded one new compound, Rimboxa (1) and three known compounds, i.e. indole-3-carboxaldehyde (2), indole-3-acetic acid (3) and 3,4-di-t-butylaniline (4). Rimboxa (1) is shown to possess the 1,2-oxathiolane core structure. 3,4-Di-t-butylaniline (4) is isolated for the first time from a natural resource. These compounds were isolated and characterised using extensive chromatographic and spectroscopic methods, and were subjected to cytotoxicity evaluations.